THE EFFECT OF ORGANIZATIONAL CULTURE AND PHYSICAL WORK ENVIRONMENT ON EMPLOYEE PERFORMANCE AT MEDAN DELI CAMAT OFFICE - Andriany, Dewi; Savithrie Ananda, Nurul (International Journal of Educational Review, Law And Social Sciences (IJERLAS), 2022)
The purpose of this study was to determine the Organizational Culture and Physical Work Environment on employee performance at the Medan Deli Sub-District Office. The approach used in this study is an associative approach. The associative approach is an approach where to find out that there is a relationship or influence between the two variables (the independent variable and the dependent variable). The population in this study were employees at the Medan Deli Sub-District Office, amounting to 60 people. The sample used in this study was taken by probability sampling method. In this study, the sample was the entire population of 60 people. The data collection technique used classical assumption test, multiple linear regression, t test, F test and coefficient of determination. Based on the results of the study, it can be concluded that there is a significant effect of workload on employee performance at the Medan Deli Sub-District Office. Simultaneously there is a significant effect between workload and supervision on employee performance at the Medan Deli Sub-District Office.